Which is better among FEV1/FVC and FEV1/SVC in obstructive airway disease? - M., Saravanan; Ramesh, P. M.; Rajarajeswari, K. (International Journal of Advances in Medicine, 2018)
Background: Forced expiratory volume in 1 second (FEV1) to forced vital capacity ratio (FVC) is being used to diagnose the obstructive lung diseases. Forced manoeuvre (FVC) or relaxed/slow manoeuvre (SVC) can be used to determine vital capacity (VC). In healthy individuals the difference between SVC and FVC (SVC-FVC) is minimal whereas in the presence of airway obstruction this difference will become significant. The present study was done with the objective to detect and compare the airway obstruction by determining the FEV1/FVC and FEV1/ SVC ratios. Methods: This was a prospective cross-sectional study done at OPD, Government Thiruvoteeswarar hospital of thoracic medicine/Kilpauk medical college during the period from September 2016 to February 2017among the patients presenting with symptoms of obstructive airway disease. The sample comprised of 353 patients who underwent spirometry according to standard of ATS/ERS guidelines. As per the criteria, the patients are classified into four groups, by spirometry. Results: The analysis of FEV1/FVC revealed the presence of airway obstruction in 131 (37%) individuals compared to 165 (46%) individuals by the analysis of Fev1/SVC ratio. In the obstruction and mixed groups, the difference in vital capacity SVC – FVC is statistically superior (p<0.05) when compared to normal and restriction groups. Conclusions: The FEV1/SVC ratio detected the presence of airway obstruction in more individuals than did FEV1/FVC ratio and hence FEV1/SVC considered as more reliable factor in the detection of obstructive airway diseases.